The Impact of Corona Virus Disease 2019 (COVID-19) on Indonesia Property Stock Index - Kevin Ronaldo Gotama; Njo Anastasia (Master of Management, School of Business and Management, Petra Christian University, 2021)
A promising investment in the property sector is due to appreciation in property value. As an economic instrument, the stock market, inseparable from different environmental factors, was triggered by incident in Wuhan, Hubei Province, China, an outbreak of acute respiratory tract infection 2 (SARS-CoV-2) in December 2019 and then spread across China. This study is a comparative study on the stock index of the property sector on the stock exchange of countries affected by the Corona Virus Disease 2019 (COVID-19) case, with a purposive sampling technique according to certain criteria for sample selection. The event analysis was performed by analyzing market reaction; with COVID-19 incident effect as one of the event tests, the stock price index. The findings of the study indicate that there is an index response to the incident of COVID-19. The reflected reaction shows in the abnormal return and trade volume activity before and after the incident. Thus, this study is expected to be taken into consideration for stock investors regarding the impact of the Corona Virus Disease 2019 (COVID-19) pandemic on stock prices, by providing an overview of changes in stock prices during the monitoring period, so that they can make investment decisions in the period before and after incident.